First karyotype description and nuclear 2C value for Myrsine (Primulaceae): comparing three species - de Carvalho, Renata Flávia (Comp Cytogenet, 2017)
Abstract. Cytogenetic studies in Primulaceae are mostly available for herbaceous species, and are focused on the chromosome number determination. An accurate karyotype characterization represents a starting point to know the morphometry and class of the chromosomes. Comparison among species within Myrsine, associating these data with the nuclear 2C value, can show changes that led the karyotype evolution. Here, we studied three Myrsine species [Myrsine coriacea (Swartz, 1788) Brown ex Roemer et Schultes, 1819, Myrsine umbellata Martius, 1841 and Myrsine parvifolia Candolle, 1841] that show different abilities to occupy the varied types of vegetation within the Brazilian Atlantic Forest. Cytogenetic characterization showed some individuals with 2n = 45 chromosomes for Myrsine parvifolia and Myrsine coriacea, with most individuals of the three species having 2n = 46. The first karyograms for Myrsine were assembled and presented morphologically identical and distinct chromosome pairs. In addition, differences in the mean 2C nuclear value and chromosome morphometry were found. Therefore, the first description of the Myrsine karyotype has been presented, as well as the nuclear 2C value. The procedures can be applied to other Myrsine species for future investigations in order to better understand its effects on the differential spatial occupation abilities shown by the species in Brazilian Atlantic Forest.